Desarrollo del pensamiento métrico a través de estrategias pedagógicas en educación matemática (2023)
This analysis focuses on pedagogical strategies to develop metric thinking in mathematics education. It examines research highlighting the importance of relating mathematics to everyday life. Strategies such as contextualization in metric environments, technology integration, cooperative learning, and interactive labs are explored in detail. Each approach has its advantages and disadvantages, and their choice should be based on specific objectives and resources. Adapting strategies to the students' cognitive level is crucial. In summary, there is no one-size-fits-all strategy; diversification and customization are key to developing a solid metric thinking.